Answer to Question #213693 in Differential Equations for amit

Question #213693

Solve the equations by the use of the operator D







D²y -6Dy +9y= e^3x + e^-3x



1
Expert's answer
2021-07-27T15:04:02-0400

"D^2y-6Dy+9y=e^{3x}+e^{-3x}"

For yn

"(D^2-6D+9)y=0\\\\m^2-6m+9=0"


"\\implies(m-3)^2=0\\\\\\implies m=3,3"


"\\\\yn=\\frac{1}{D^2-6D+9}(e^{3x}+e^{-3x})"


"\\\\=\\frac{e^{3x}}{D^2-6D+9}+\\frac{e^{-3x}}{D^2-6D+9}"


"=\\frac{xe^{3x}}{2D-6}+\\frac{e^{-3x}}{36}"


So solution is "y(x)=y_n+y_p"


"\\implies y(x)=ae^{3x}+c_2xe^{3x}+\\frac{x^2e^{3x}}{2}+\\frac{e^{-3x}}{36}"


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog